The Relationship between Teacher Interpersonal Interaction and the Biology Learning Environment in Senior High Schools - Sanusih, Dhea Khoiriyah; Zulfiani, Zulfiani (International Journal of Biology Education Towards Sustainable Development, 2025)
Biology learning that focuses more on conveying material concepts results in less classroom interaction. Each teacher's interaction skills vary, thus creating a different quality of learning environment. An ideal learning environment should stimulate curiosity and encourage active student involvement. To achieve this condition, the interpersonal interaction factor of teachers is an important variable that needs to be examined. This study was conducted with the primary focus of analyzing the relationship between teacher interpersonal interaction and the biology learning environment in Senior High Schools in South Tangerang City. The research method used was a survey with correlational techniques. There were 96 students as samples from seven different schools using the Cluster area sampling technique. Data were collected through questionnaires, specifically the Questionnaire on Teacher Interaction (QTI) and "What Is Happening In This Class?" (WIHIC). The study's results showed a positive and significant relationship between teacher interpersonal interaction and the biology learning environment. Teacher interpersonal interaction accounted for 5.85% of the quality of the biology learning environment, with the remaining quality influenced by other factors. The teacher's interpersonal interaction and the biology learning environment were categorized as moderate, with percentages of 80% and 73%, respectively. It is recommended that teachers develop interpersonal interaction skills and implement more interactive teaching approaches to improve the quality of the biology learning environment.